Kartun Humor dan Misi Dakwah dalam Media Cetak - Satrio Adhitama, Tias (Jurnal Komunikasi Islam, 2014)
This article discusses the gag cartoon in the study of proselytizing. The mass media has a particular rubric for the readers to share their best works of Cartoons. The paper argues that jokes-based Cartoons develop significant values for the proliferation of moral and spiritual messages. For this purpose, these Cartoons should comply with, at least, two principles. First, the Cartoons are deliberately created through the solemn contemplation relying on divine values. Second, the Cartoons are presented within the confines of, and in line with, educational purposes. Both principles maintain the quality of humor in accordance with ethical and aesthetic criteria.Keywords: cartoon humor, proselytizing, print media----------------------------------------------------------------------Paper ini mengulas kartun humor (gag cartoon) dalam kajian dakwah. Seorang kartunis yang bertanggung jawab sadar bahwa karya yang lahir dari tangannya harus memiliki nilai-nilai manfaat. Pertama, karya tersebut sengaja diciptakan melalui kontemplasi yang khusyuk bersandar pada nilai-nilai Ilahiyah. Kedua, kelucuan kartun yang dihadirkan harusnya dalam batas-batas yang edukatif. Kedua hal tersebut untuk menjadikan kualitas humor senantiasa sehat jika dilihat dari humor kriterium etis dan dikategorikan sebagai humor meninggi dalam kriterium estetisnya.Kata Kunci: kartun humor, dakwah, media cetak.